FUNDAMENTALIST DA’WAH MOVEMENT: THE STUDY OF LOCAL TABLIGHI JAMA’AH GROUP AND ITS ACCEPTANCE IN MADURA - Arif Zamhari; Ahsan Riadi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
This paper analyzes the form of religious fundamentalism displayed through Tablighi Jama'ah’s da’wah movement in Madura and uncovers the rationale for Madura’s community's acceptance of this da’wah movement group. This paper is qualitative research using a case study approach. Data collection was carried out through interviews with some main figures and followers of the group, a series of observations, and documentation of the da’wah activities undergone by the group. The result shows that the Tablighi Jama'ah’s da’wah movement in Madura can be categorized as a puritanical Islamic fundamentalist movement, particularly because it intends to purify faith, sharia, and morals. In contrast to the beliefs of other religious groups, this group prohibits an active and massive use of technology because it is perceived as a direct obstacle to da’wah and is considered full of immorality. This group emphasizes the so-called sunnah appearance, such as using robes, turbans, siwak, cingkrang trousers, and not being engaged in practical politics. Moreover, they also emphasize congregational prayers and the necessity of living a simple life. This paper also signifies that the Madura community accepts the Tablighi Jama'ah because their religious practices are congruently aligned with the teachings of Ahlus Sunnah Wal Jama'ah. In addition, the acceptance of the Madura community is due to their obedience toward the Kiai, who have previously accepted the Tablighi Jama'ah da’wah activities in Madura.